The Universal Degrees (Marâtib), Manifestations (Mazâhir) and Divine Presences (Hadharât) of The Existence in Ibn Arabi’s School of Mysticism - Abulfazel Kiashemshaki (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2011)
One of the most elemental discussions in ‘irfân nadzâri (theoretical mysticism), in the section where its adherents discuss ontology, is the debate surrounding the degrees of God’s manifestation. The reason for this is that in the mystic’s view real existence, or the reality of existence, is the existence of the Truth (i.e. God) who manifests Himself in the degrees and mirrors that are the manifold creatures of the world.